Penggunaan Aplikasi iPusnas Untuk Meningkatkan Keterampilan Berbahasa Indonesia Di SMK Negeri 1 Lubuk Pakam - Sarma Panggabean; Intan Galingging; Anggi Panggabean; Agustina Sihite; Marito Kristina Ambarita (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
Community service (PkM) carried out by FKIP students at HKBP Nommensen University in Medan with their supervisors is the use of the iPusnas application to improve Indonesian language skills. The iPusnas application is a digital library application with social media features offered by the National Library of the Republic of Indonesia (Bungin, 2017). The iPusnas application can be used by users as a means of information retrieval so that users do not need to bother getting information and collections in the library. The implementation of activities to improve students' language skills at SMK Negeri 1 Lubuk Pakam uses practical methods. The iPusnas application can be used by users as a means of information retrieval so that users do not need to bother getting information and collections in the library. The benefits of socializing the use of the iPusnas application can improve Indonesian language skills at SMK Negeri 1 Lubuk Pakam. Students can study more intensively and develop their abilities, especially in language skills, so it is recommended that training and guidance activities on using the iPusnas application can continue to be carried out regularly so that they are more effective.